Perilaku Peternak terhadap Risiko Produksi Usaha Ternak Ayam Broiler di Kabupaten Sintang - E Valentina; Maswadi; A Suharyani (Politeknik Negeri Lampung, 2026)
This study aims to analyze the production risk levels of broiler farming under partnership and independent systems in Sintang Regency, and to assess farmers’ behavior toward production risks. The study employed a quantitative descriptive method using the Moscardi dan de Janvry risk factor model. The respondents comprised 60 farmers, including 30 partnership-system farmers and 30 independent-system farmers. The results indicate that production risk is lower in the partnership system than in the independent system, and that most farmers are risk lovers. These findings can serve as a basis for risk mitigation strategies for broiler chicken farmers in Sintang Regency